Austerity, cyclical adjustment and the remaining leeway for expansionary fiscal policies within the current EU fiscal framework - Achim Truger (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2015)
Fiscal policy in the Euro area is still dominated by austerity measures implemented under the institutional setting of the 'reformed' stability and growth pact, and the even stricter 'fiscal compact'. At the same time, calls for a more expansionary fiscal policy to overcome the economic crisis have recently become more frequent. In his Jackson Hole speech Mario Draghi, the president of the ECB, called for a more expansionary fiscal stance for the Euro area as a whole and a public investment programme on the European level insisting, however, that the existing rules of the Stability and Growth Pact be respected. The European Council at its meeting in June 2014 also saw the need to stimulate growth, but insisted as well that this be realised within the current institutional framework. Recently, the EU-Commission in this spirit has launched the Juncker-Plan to stimulate (public) investment and is using a less strict interpretation of the Stability and Growth Pact in order to provide more fiscal leeway for countries under unfavourable economic circumstances. The paper argues that these steps do not go far enough and that a truly expansionary fiscal policy in the dimension of two to three per cent of Euro area GDP for a few years is possible even within the existing institutional framework. Special emphasis is put on the method of cyclical adjustment employed by the European Commission in order to assess member states' fiscal position and effort as well as on ways to increase public investment. It will be shown that even in the existing framework the leeway for a macro economically and socially more sensible fiscal policy using the interpretational leeway inherent in the rules could be quite substantial.
Keywords: E61; E62; E65; H62; H63; 330; fiscal policy; austerity; cyclical adjustment of public finances; Euro area